The un/methodology of 'theoretical intuitions': resources of generations gone before, thinking and feeling class. Issue 1 (2nd January 2021) - Hey, Valerie; Leaney, Sarah; Leyton, Daniel
ABSTRACT: Class Matters, by Mahony and Zmroczek (1997), was an important collection marking working-class women's contribution to the academy and society. In taking up the question of class, this paper considers the ways in which a partial and particular discourse reflected its author's material circumstances, including her preferred conceptual interests as well as her un(self)conscious knowledge. In revisiting the way class 'mattered', and continues to matter – we devised and enacted an exploratory dialogical methodology to open up the original text to new meanings and interpretations influenced by generationally and geographically specific intellectual/theoretical vocabularies. The paper enacts this multivocality with reflections from each author, connected by a co-authored exploration of affect and the power and problematic of the 'autobiography of the question'.